Developing a Coding Scheme for Exploring Preservice Science Teachers’ Metacognition in A Method Course - Sanium S. (2023)
Promoting metacognition in preservice science teachers (PSTs) is necessary for effective science teaching. However, metacognition is an abstract attribute that requires in-depth investiga-tions with qualitative methods. This study aimed to express the process utilized to develop a coding scheme of PSTs’ metacognition (CSPM). Methods: This study started with a review of the metacog-nition conceptual framework. Next, the researchers collected data about PSTs’ metacognition from a metacognitive self-report (MS) and a metacognition interview protocol (MIP). The participants were 22 third-year PSTs who studied at one public university. All data were analyzed for codes by using content analysis. Results: The CSPM consisted of 177 codes that can be divided into two main components and six subcomponents. The validity of the CSPM was checked by a panel of experts through the item–objective congruence index (IOC) into two different levels: an IOC between codes and components of metacognition, and an IOC between codes and levels of metacognition. The IOCs of the CSPM in the two levels were acceptable. In conclusion, the CPSM was a qualified coding scheme for qualitatively analyzing metacognition in PSTs as well as other types of participants. This study also pointed out an urgent need to develop metacognition in PSTs.